Language and education policy as one of the main challenges of migrant integration in Poland - Wąsikiewicz-Firlej, Emilia (Glottodidactica, 2021)
This article aims to map current state policy and governmental responses to migrant integration in Poland, as well as to identify pressing needs and key challenges in this area, with a particular focus on language and education. It draws on a literature review and analysis of legal documents and reports on migrant integration and language policy for 1989–2020. When analysing the data, particular attention was paid to the declared state policy on migrant integration and its actual implementation, as captured in the Supreme Audit Office (NIK 2015, 2020) and Migrant Integration Policy Index reports (MIPEX 2015, 2020). The research shows that the scope of integration activities and their effects have been unsatisfactory to date. The situation of migrants in Poland was dubbed “equality on paper” in the MIPEX 2020 report. Current programmes and activities are not fostering full integration of migrants. Apart from housing and employment issues, a lack of language skills and education that is not responsive to the needs of migrants remain the main barriers to migrant integration in Poland.